MULTI-DIMENSIONAL ASSESSMENT OF INVESTMENT CLIMATE: LESSONS FROM DEVELOPING COUNTRIES FOR UZBEKISTAN’S FDI POLICY - Khaydarov Khurshidbek Latipjonovich (The Conference Hub, 2025)
In an era of intensified globalization and accelerating capital mobility, the ability of developing countries to attract foreign direct investment (FDI) has emerged as a decisive factor in shaping their economic trajectory. FDI is no longer perceived merely as a source of capital inflow; rather, it is recognized as a multidimensional instrument that facilitates the transfer of advanced technologies, management practices, access to global markets, and sustainable employment opportunities. For many emerging economies, FDI serves as a strategic lever to close developmental gaps, enhance industrial competitiveness, and diversify their economic base.However, the global landscape for attracting investment has become increasingly competitive and complex. As capital becomes more selective and risk-sensitive, traditional incentives such as tax holidays and cheap labor are no longer sufficient to ensure sustained investor interest. Instead, institutional quality, governance standards, macroeconomic stability, and the efficiency of infrastructure systems have become critical determinants of a country’s investment attractiveness. These elements not only influence the perception of risk but also shape the long-term viability of investment projects.